VALUE CO-CREATION THROUGH SERVICE PORTFOLIO DESIGNING IN WELLNESS INDUSTRY Case Wasa Wellness - Peltoniemi, Kristiina (My University, 2015)
In today’s society and economy the growing interest towards wellbeing and health is significant; rise of the Wellness- phenomenon is one of the signs of this. In today’s economy the importance of health and wellness of the employees from the perspective of employer is increasing. In 2014 Finnish corporations has invested approximately 726 Euros per person for the work welfare. The research question that is aimed to reach through the specific objectives is: how to meet the needs of Finnish corporations as group (TYKY / TYHY / other) with wellness services (*not including healthcare)? What is valued and what is the need? The theoretical framework for the study is based on the theory of service designing, service dominant logic, value formation and the concept of the wellness service. Hermeneutical research approach philosophy is used, empirical study is qualitative, and the study is in a form of instrumental case study as it seeks to issue an outcome of generalization. Semi-structured interviews and benchmarking are conducted to proceed in the service development of the wellness portfolios. The budget and values and needs of the target segment were explored. What was understood through the study was that the content of the service packages has specific similar elements and the main service/services can wary as long as needs are fulfilled. The important factors besides meeting and offering for the needs are in the touch points and in wellness industry’s ideology itself. Through the elements of wellness categories the intangible benefits and emotional needs of the customer might be able to reach not only with the main service but also with everything that includes to the whole service experience. Outcome of customization came relevant if there were many services available from where to form the package; this also adds value for both to the buyer and service provider. The implementation guidelines and business plans were also given for the whole wellness industry and case company.
Keywords: Service concept; Value formation; Service designing; Value co-creation; Wellness industry; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|